Association of fasting glucose with lifetime risk of incident heart failure: the Lifetime Risk Pooling Project - Sinha, Arjun (Cardiovasc Diabetol, 2021)
BACKGROUND: Given the rising prevalence of dysglycemia and disparities in heart failure (HF) burden, we determined race- and sex-specific lifetime risk of HF across the spectrum of fasting plasma glucose (FPG). METHODS: Individual-level data from adults without baseline HF was pooled from 6 population-based cohorts. Modified Kaplan–Meier analysis, Cox models adjusted for the competing risk of death, and Irwin’s restricted mean were used to estimate the lifetime risk, adjusted hazard ratio (aHR), and years lived free from HF in middle-aged (40–59 years) and older (60–79 years) adults with FPG < 100 mg/dL, prediabetes (FPG 100–125 mg/dL) and diabetes (FPG ≥ 126 mg/dL or on antihyperglycemic agents) across race-sex groups. RESULTS: In 40,117 participants with 638,910 person-years of follow-up, 4846 cases of incident HF occurred. The lifetime risk of HF was significantly higher among middle-aged White adults and Black women with prediabetes (range: 6.1% [95% CI 4.8%, 7.4%] to 10.8% [95% CI 8.3%, 13.4%]) compared with normoglycemic adults (range: 3.5% [95% CI 3.0%, 4.1%] to 6.5% [95% CI 4.9%, 8.1%]). Middle-aged Black women with diabetes had the highest lifetime risk (32.4% [95% CI 26.0%, 38.7%]) and aHR (4.0 [95% CI 3.0, 5.4]) for HF across race-sex groups. Middle-aged adults with prediabetes and diabetes lived on average 0.9–1.6 and 4.1–6.0 fewer years free from HF, respectively. Findings were similar in older adults except older Black women with prediabetes did not have a higher lifetime risk of HF. CONCLUSIONS: Prediabetes was associated with higher lifetime risk of HF in middle-aged White adults and Black women, with the association attenuating in older Black women. Black women with diabetes had the highest lifetime risk of HF compared with other race-sex groups. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12933-021-01265-y.